Molecular manipulation with atomic force microscopy - Duwez, Anne-Sophie.; Willet, Nicolas (Boca Raton : CRC Press, 2011)
"The manipulation of molecules is an active area of research with applications in chemistry, biology, physics, engineering, and polymer science. This book provides a comprehensive review of single molecule manipulation with atomic force microscopy (AFM). The text demonstrates that AFMs are capable of meeting the three main challenges in molecular manufacturing: manipulating and positioning each atom or molecule in the right place, making the atom or molecule form certain bonds, and achieving high-throughput fabrication. New and experienced researchers will find a wealth of information in this informative volume which demonstrates the potential of AFMs beyond imaging"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Nanotechnology -- Research; Atomic force microscopy -- Industrial applications; Molecular dynamics; Electronic books